ANALISIS STRATEGI PRODUK SMART PANIN PADA PT. PANIN BANK, TBK - Yudhanto, Arief; Nugraha, Hari Susanta; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2013)
Companies have a tendency to compete with other companies engaged in similar business. Company in order to maintain its viability in order to survive in the competitive climate should have a strategy in creating products of excellence to attract consumers to switch to its products. In conducting its business, the Panin Bank’s product namely SMART Integration compete with others who have similar products. To face the competition so that product development strategy is needed to achieve corporate goals. The purpose of this study was to determine the company's strategic alternatives in developing SMART products Panin using SWOT analysis. This research is a descriptive study with qualitative data support. Data collection techniques gained through in-depth interviews as well as real data in the field of internal and external. Based on the results of the SWOT analysis, the resulting nine alternative strategy, namely (1) Carry out a good promotional activities so that potential customers know SMART Panin; (2) Maintain and improve the position of the national rankings in order to improve the bank's reputation in the eyes of the public; (3) Making changes more flexible system in particular in the field of revenue assurance; (4) Increase the number of KCU order to facilitate prospective customers when credit agreement; (5) Conduct an attractive promotions that keep customers willing to put their money in the bank; (6) provide an interesting variety of products as well as competitive rates; (7) Taking more policy refers to the ease of customers; (8) Improving and promoting attractive; (9) Continuously innovate as a form of readiness to compete with other banks.